2018
DOI: 10.1021/acsanm.8b01377
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescence Modulation of Refolded DNA Aptamer-Functionalized Single-Walled Carbon Nanotubes for Optical Sensing

Abstract: Selective modulation of near-infrared (NIR) fluorescence of single-walled carbon nanotubes (SWNTs) is important for their applications as NIR optical sensors and devices. Here, we study the target-molecule-mediated NIR fluorescence modulation of refolded DNA aptamer-functionalized SWNTs, using platelet-derived growth factor (PDGF) and a PDGF-binding aptamer as a model system. The aptamer–SWNT complexes use SWNT as nanoscale NIR optical emitters and DNA aptamers as molecular recognition elements. The binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Aptamers are synthetic single-stranded oligonucleotides without the periodic sequence and enable the recognition of a targeting protein through specific noncovalent interaction between the two entities, followed by partially structural conformation or 3-dimensional shape folding . High selectivity, specificity, and affinity of aptamers offer equal or superior biosensing capabilities to those of enzyme and antibodies which are relatively unstable with high production cost. Regarding optical sensing, graphene or graphene oxide nanosheets with aptamers exhibit multiple imaging with strong loading ability using DNA/RNA aptamer probes because of high surface-to-thickness ratio, in which a biocompatible sensing platform with strong fluorescence quenching has been demonstrated through fluorescence resonance energy transfer (FRET) from the fluorophore constitutes. Recently, label-free optical biosensor using Aptamer-SWNT hybrids platform demonstrates the detection of a target protein via large near-infrared fluorescent emission quenching or enhancing responses. The aptamer-protein interaction enables the proximity of the protein to semiconducting SWNT to lead to the excited-electron transfer from the covalent band of SWNTs to LUMO of molecules/proteins for quenching effect and/or produces a change in the local dielectric environment of the SWNT for enhancing recognition. In this context, the allowance of aptamers folding on SWNTs is critical to the detection of a target protein without aptamer detachment from SWNTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aptamers are synthetic single-stranded oligonucleotides without the periodic sequence and enable the recognition of a targeting protein through specific noncovalent interaction between the two entities, followed by partially structural conformation or 3-dimensional shape folding . High selectivity, specificity, and affinity of aptamers offer equal or superior biosensing capabilities to those of enzyme and antibodies which are relatively unstable with high production cost. Regarding optical sensing, graphene or graphene oxide nanosheets with aptamers exhibit multiple imaging with strong loading ability using DNA/RNA aptamer probes because of high surface-to-thickness ratio, in which a biocompatible sensing platform with strong fluorescence quenching has been demonstrated through fluorescence resonance energy transfer (FRET) from the fluorophore constitutes. Recently, label-free optical biosensor using Aptamer-SWNT hybrids platform demonstrates the detection of a target protein via large near-infrared fluorescent emission quenching or enhancing responses. The aptamer-protein interaction enables the proximity of the protein to semiconducting SWNT to lead to the excited-electron transfer from the covalent band of SWNTs to LUMO of molecules/proteins for quenching effect and/or produces a change in the local dielectric environment of the SWNT for enhancing recognition. In this context, the allowance of aptamers folding on SWNTs is critical to the detection of a target protein without aptamer detachment from SWNTs.…”
mentioning
confidence: 99%
“…In this context, the allowance of aptamers folding on SWNTs is critical to the detection of a target protein without aptamer detachment from SWNTs. It is recently reported that the refolding evolution of the Aptamer-SWNT hybrids through ligand exchange wrapping methods under the controlled conditions, including thermal-assisted denaturation for refolding aptamer on SWNT, incubation time allowing for appropriately refolded aptamer on SWNT to enhance optical biosensing, and reversible sensing modules within an alginate hydrogel matrix …”
mentioning
confidence: 99%
“…The disulfide bonds formed during storage are reduced with TCEP. Through a refolding process [ 44 ], these aptamers are returned to their 3D confirmation with a specific binding affinity to the spike protein. Subsequently, the aptamers are immobilized on a flat gold-coated glass slide.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies carried out by Landry et al and Lee et al have shown that DNA aptamers on SWCNT scaffolds can be used to detect certain biologically relevant proteins (Landry et al, 2017; Lee et al, 2018). This label-free fluorescence detection offers many advantages over conventional immunological analytical methods, such as enzyme-linked immunosorbent assays (ELISA) or mass spectroscopy, which lack temporal resolution for real-time quantification of protein levels.…”
Section: Biopolymer-suspended Swcntsmentioning
confidence: 99%
“…Furthermore, this method obviates cumbersome purification and labeling steps typically required by more classical approaches. Both RAP1 and HIV-1 (Landry et al, 2017) and platelet-derived growth factor (PDGF) (Lee et al, 2018) were successfully detected using DNA aptamer-SWCNT complexes. Moreover, the RAP1 and HIV-1 sensors were also reported to selectively respond to their target proteins in molecularly complex environments, such as crude, unpurified cell lysates (Landry et al, 2017).…”
Section: Biopolymer-suspended Swcntsmentioning
confidence: 99%